Bunkering down? The geography of elite residential basement development in London. Issue 9 (21st October 2022) - Burrows, Roger; Graham, Stephen; Wilson, Alexander
ABSTRACT: Much has been written about the "luxified skies" – "high-rise", "super-prime" housing for the super-rich – that has been sprouting up across London. Thus far, less attention has been paid to what has been happening to the subterranean city. The "luxified skies" are highly visible reminders of elite "verticality" but, what we might term, "luxified troglodytism" is also an important aspect of London's changing geometries of wealth, power and architecture. In this paper, we map out in detail the emerging subterranean geography of residential basement development across London since 2008. The very wealthy, it turns out, have been "bunkering down" across certain parts of London, to an extent hitherto little understood. Some 7, 328 new residential basements underneath existing houses had been granted planning permission up to late-2019. Over 1, 500 of them are of a size that their locations might best be thought of as marking out a distinct plutocratic "basement belt".